CREATING OF SPORTS MAPS FOR SECONDARY SCHOOL - GRYNIUK, Oleg; YURIEVA, Antonina (Bulletin of Taras Shevchenko National University of Kyiv, Geography, 2024)
Background. Modern education is impossible to imagine without gaining practical skills and abilities that are difficult to obtain only in the classrooms of the school. Training that forms practical competencies is more effective. Orienteering is a type of activity that combines physical, practical and intellectual components. This is effortless to do when organizing training sessions "plain air" in the green areas adjacent to university buildings. However, the deficit of appropriate cartographic material, namely the quality sports maps, prevents such training sessions for students. Thus, it is relevant to study the functionality of available GIS software. The purpose of this study is to reveal the possibility of using and the availability of sports orientation in general secondary education institutions and to develop an algorithm for creating a map and a route for conducting orientation with students on the example of Tetiiv Lyceum No. 2 of the Kyiv region.Methods. The research methodology is based on the analysis and generalization of geo-information software for creating sports maps, the analysis of the suitability of satellite images of the territory of Ukraine and other cartographic materials. The GIS mapping method was used - from the selection of the optimal projection and the corresponding coordinate system to the creation of a sports map in the Open Orienteering Mapper program.Results. The main stages of creating a sports map are: preparing the base map; mapping the territory - creating a map;distance planning;preparing the map for printing. To create a substrate, we recommend using the "SASPlanet" program. You can use the "Open Orienteering" program to create an actual cartographic work - a sports map. It is better to plan, create a race distance, design and prepare a map for printing in the "Purple Pen" program. The algorithm for creating a sports map with the possibility of further mapping with the help of free GIS support is presented on the example of the territory of the town of Tetiiv, Kyiv region.Conclusions. The practical significance and novelty lies in the fact that an algorithm and toolkit are presented for the full organization of classes, the acquisition of practical skills, and the holding of orienteering competitions on the territory of an educational institution.
Keywords: orienteering; sports map; secondary school; GIS; Open Orienteering Mapper